2018
DOI: 10.3847/1538-4365/aac2e0
|View full text |Cite
|
Sign up to set email alerts
|

Planck Cold Clumps in the λ Orionis Complex. II. Environmental Effects on Core Formation

Abstract: Based on the 850 µm dust continuum data from SCUBA-2 at James Clerk Maxwell Telescope (JCMT), we compare overall properties of Planck Galactic Cold Clumps (PGCCs) in the λ Orionis cloud to those of PGCCs in the Orion A and B clouds. The Orion A and B clouds are well known active star-forming regions, while the λ Orionis cloud has

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(89 citation statements)
references
References 47 publications
3
86
0
Order By: Relevance
“…The SCOPE survey discovered more than 3,000 PGCC cores across the Galaxy at 850 µm with SCUBA- 2 (Submillimetre Common-User Bolometer Array 2) on board JCMT (e.g., Yi et al 2018;Eden et al 2019). Yi et al (2018) identified 119 cores embedded in 96 PGCCs in the Orion region from JCMT SCOPE data and JCMT archive data. Eden et al (2019) released a compact source catalog using the JCMT SCOPE data, which contains 3,528 cores identified in 1,235 PGCCs from the Galactic plane to high latitudes.…”
Section: Sample Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SCOPE survey discovered more than 3,000 PGCC cores across the Galaxy at 850 µm with SCUBA- 2 (Submillimetre Common-User Bolometer Array 2) on board JCMT (e.g., Yi et al 2018;Eden et al 2019). Yi et al (2018) identified 119 cores embedded in 96 PGCCs in the Orion region from JCMT SCOPE data and JCMT archive data. Eden et al (2019) released a compact source catalog using the JCMT SCOPE data, which contains 3,528 cores identified in 1,235 PGCCs from the Galactic plane to high latitudes.…”
Section: Sample Selectionmentioning
confidence: 99%
“…Figure 1 shows the Galactic distribution of 207 SCUBA-2 cores, and the information on the targets is summarized in Table 1 with the core name, coordinate, dust temperature, H 2 column density, type of environment, and the related PGCC. The dust temperature is taken from the PGCC catalog and the H 2 column density is derived from the 850 µm peak intensity of the PGCC core (Yi et al 2018;Eden et al 2019) and the dust temperature. The 207 SCUBA-2 cores have dust temperatures rang-ing from 9.2 K to 22.4 K with the median value of 13.3 K. They have H 2 column densities of (0.17-12)×10 23 cm −2 with the median value of 8.2×10 22 cm −2 .…”
Section: Sample Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple papers have already been published using the SCOPE data, namely the maps and images (Liu et al 2016;Kim et al 2017;Tatematsu et al 2017;Juvela et al 2018a;Juvela et al 2018b;Liu et al 2018a,b;Tang et al 2018;Yi et al 2018;Zhang et al 2018).…”
Section: Scope Science Goalsmentioning
confidence: 99%
“…Liu et al 2013;Meng, Wu & Liu 2013;Parikka et al 2015;Zhang et al 2016;Fehér et al 2017), as well as detections of line emission from dense gas tracers (Yuan et al 2016). There can be, however, low levels of active star formation within PGCCs (Tóth et al 2014;Liu et al 2015;Tang et al 2018;Yi et al 2018;Zhang et al 2018).…”
Section: Introductionmentioning
confidence: 99%